IL-18 as a biomarker linking systemic juvenile idiopathic arthritis and macrophage activation syndrome. (20th July 2019) - Yasin, Shima; Fall, Ndate; Brown, Rachel A; Henderlight, Maggie; Canna, Scott W; Girard-Guyonvarc'h, Charlotte; Gabay, Cem; Grom, Alexei A; Schulert, Grant S
Abstract: Objectives: Systemic juvenile idiopathic arthritis (sJIA) is a childhood arthritis with features of autoinflammation and high risk of macrophage activation syndrome (MAS). IL-18 has been shown to have key roles in sJIA and MAS. We aimed to examine IL-18 levels in sJIA in relation to disease activity and history of MAS and other disease biomarkers namely S100 proteins and CXCL9. Methods: Total IL-18, CXCL9 and S100 proteins levels were determined in 40 sJIA patients, and IL-18 levels were compared between patients with regards to disease activity, history of MAS, and other biomarkers. Results: Total IL-18 levels were significantly higher in patients with active sJIA (median 16 499 pg/ml; interquartile range (IQR) 4816–61 839), and remained persistently elevated even in the majority of patients with inactive disease (1164 pg/ml; IQR 587–3444). Patients with history of MAS had significantly higher IL-18 levels (13 380 pg/ml; IQR 4212–62 628) as compared with those without MAS history (956.5 pg/ml; IQR 276.3–4262.5). Total IL-18 performed well with area under the curve of 0.8145 and 0.84 in predicting disease activity and history of MAS, respectively. We observed moderate correlation between IL-18 and CXCL9 ( R = 0.56), S100A8/A9 ( R = 0.47) and S100A12 ( R = 0.46). The correlation was stronger for ferritin ( R = 0.74) and overall for those with active disease. Conclusion: Total IL-18 levels were elevated in the majority of sJIA patients regardless of clinical features, but were higher in patients with active disease and history of MAS. Change in IL-18 may reflect increased disease activity or development of MAS.